How to Reduce Work-Related Road Deaths? Driver Fatigue Monitoring – Case Study - Jelica DAVIDOVIĆ; Dalibor PEŠIĆ; Boris ANTIĆ (Promet (Zagreb))
Work-related road deaths are the leading cause of occupational death. These traffic accidents contribute to at least one quarter all work-related deaths. Key risk factors associated with driving for work are driver fatigue and speeding. Driver fatigue is the growing problem of the new era. Due to traffic exposure, commercial vehicles are identified as a particularly risky category. According to traffic accident data, depending on the country, the percentage of traffic accidents caused by driver fatigue ranges up to 40%. In this paper, we used a unique procedure for identifying fatigue based on eleven factors, using expert knowledge, budget allocation and the composite rank method. The case study was realised in the Republic of Serbia, which is a country with a huge professional drivers deficiency problem. The main objective of this paper is to present an approach to reducing work-related road deaths to reach vision zero, based on a model for identifying commercial vehicle driver fatigue before the drivers start their shift. The advantage of this model is that it does not distract the driver in any way while driving and is based on objective data. It does not require recording the driver with a camera or hooking up to an electrode to record heart or brain activity.